INDONESIAN INTERNATIONAL RELATIONS OFFICE MANAGERS PERCEPTIONS ON MANAGEMENT COMPETENCIES - Azzam Hassan Mohamed (International Interdisciplinary Conference on Sustainable Development Goals, 2022)
The purpose of the current study was to explore Indonesian international relations office managers perspectives on management competencies. The study was conducted utilizing constructivist grounded theory methods and a constructivist viewpoint. . The participants in this study were current managers of foreign offices in Indonesian universities; the sample comprised of international office managers both from public and private universities, as well as small and large universities in terms of student population. Results also shows that; what makes a competent international office manager is a mix of core and professional competences that can make a manager standout “relativity similar to (Pham et al., 2019)”. meritocracy and nepotism are in balance when it comes to the nomination and selection of the IOMs, plus managed to create a job description that emerged from the participants’ experiences, the international relations office in Indonesian HEIs is considered a middle unit below vice rectors, a model was created to perceive the competencies ought to be in a competent international office manager. The author urges a review of the internationalization strategy on the national level; the current one is just a general guideline and does not cover or manage the complexity of the current scene.